Copper(II)-Dioxygen Facilitated Activation of Nitromethane: Nitrogen Donors for the Synthesis of Substituted 2-Hydroxyimino-2-phenylacetonitriles and Phthalimides - Xiang, Shiqun; Li, Yinghua; Fan, Weibin; Jin, Jiang; Zhang, Wei; Huang, Deguang (Frontiers in Chemistry, 2021)
A simple and efficient method is explored for the synthesis of 2-hydroxyimino-2-phenylacetonitriles (2) and phthalimides (4), by using nitromethane as nitrogen donors. Both reactions are promoted by Cu(II) system with the participation of dioxygen as oxidant. The scope of the method has been successfully demonstrated with a total of 51 examples. The flexible and diversified characteristics of reactions are introduced in term of electronic effect, steric effect, position of substituted groups and intramolecular charge transfer. Experimental studies suggest that the methyl nitrite could be a precursor in the path to the final products. A possible reaction mechanism is proposed, including the Cu(II)/O2−facilitated transformation of nitromethane to methyl nitrite, the base-induced formation of 2-hydroxyimino-2-phenylacetonitriles, and the base-dioxygen-promoted formation of phthalimides.